(untitled) (Journal of the College of Basic Education, 2019)
The aim of this research is to investigate the problems faced by students in adopting and accepting the use of e-learning in higher education institutions at the University of Technology (UOT). Many researchers have used the factors influencing the acceptance of technology for the perceived usefulness and the perceived ease of use of students’ intention to use technology. These factors are used to determine their impact on the acceptance and use of e-learning model provided by the University of Technology. This study seeks to expand the model by suggesting a set of examining variables that can affect both perceived utility and perceived ease of use. In addition to testing the developed model on the use of adopting e-learning in higher education based on a sample of behavior intention of students in UOT. A questionnaire conducted to the students of two collages: computer science and software engineering departments with 258-returned recording 52.2% return rate. The collected data analyzed using SPSS 24 and Excel 2017. To evaluate the measurement and structure the model, the Structural Equation Modeling (SEM) used. The finding showed that the value of the social norm(α=0.83, p<0.05) highly predicted perceived usefulness(α=0.73, p<0.05) also highly predicts perceived ease of use, but, behavior intention(BI) was highly effective by the value of the social norm(SN), perceived usefulness, perceived of easy to use. The behavior intention highly predicts by BI (α=0.17, p<0.05).It was found that the percentage of variance for students in the intention to use e-learning was 38%.